Pengaruh Rasio Keuangan Terhadap Financial Distress pada Industri Food And Beverage di Bursa Efek Indonesia Periode 2017-2019 - Dwi Nurhayati; Riana R Dewi; Rosa Nikmatul Fajri (Ekonomis: Journal of Economics and Business, 2021)
This study aims to determine the effect of profitability, leverage, liquidity, and cash flow on financial distress. This study uses a logistic regression data analysis method with the help of the SPSS version 21 program. The population in this study were 19 food and beverage companies on the Indonesia Stock Exchange (BEI) from 2017-2019. The data used in this study is secondary data obtained from financial reports published by the company from the website (www.idx.co.id). The sample was determined by the purposive sampling method, which is based on the criteria set and obtained as many as 19 companies where the research was conducted for 3 years so that 57 samples were obtained consisting of 15 companies that experienced financial distress and 42 companies that were non-distressing. The results of this research indicate that profitability, leverage and liquidity have no effect on financial distress while cash flow variables have an effect on financial distress. The results of this research are expected to be additional consideration in making company decisions in managing the company in order to avoid financial distress. And can be additional information for users of financial statements for consideration of investment decisions